Heritage conservation futures in an age of shifting global power. (October 2014) - Winter, Tim
This article argues that international conservation and heritage governance are now entering new and historically important phases. The economic and political shifts that characterize globalization today are providing a platform for non-Western modes of heritage governance to gain newfound legitimacy on the international stage. With the appropriation of cultural heritage for commercial and political purposes occurring at all levels within the emerging economies of Asia, South America, the Middle East, and Africa, heritage conservation aid now plays an important role in the cultural diplomacy and soft power strategies of numerous countries in these regions. Analyses of the globalization of heritage governance in the mid–late 20th century have focused primarily on intergovernmental bodies, such as UNESCO, at the expense of critically reading the role nation-states continue to play in international conservation and heritage governance policy. Using examples from Asia, this paper addresses this imbalance by re-centering the nation-state in an account that argues the rise of heritage diplomacy, coupled with today's shifting global order and ongoing reduction in UNESCO's capacity, hold important implications for heritage conservation over the coming decades.